In Freedom's Cause A Record of the Men of Hawaii Who Died in the Second World War - Murphy, Thomas D. (University of Hawai'i Press, 1949)
Eight hundred and six of Hawaii's sons gave their lives while serving in the armed forces of the United States during the Second World War. In Freedom's Cause is a tribute and a memorial to these men. For this roll of honor, the compilers have tried to secure biographical data and photographs of all men of Hawaii who died in military service between December 7, 1941, and December 31, 1946, when President Harry S. Truman proclaimed the termination of hostilities. Collection of these records started almost as soon as the Hawaii War Records Depository was established at the University of Hawaii in the spring of 1943. The Depository, set up as a result of cooperative action on the part of members of the faculty of the University, territorial legislators, and other public leaders, was authorized to collect and preserve all available historical records pertaining to Hawaii's participation in World War II. One of its first projects was to assemble a file of biographical data on men who had died in military service, which would become one of many sources from which information for this volume was gathered.